A multicenter study evaluating the effectiveness and safety of single‐dose low molecular weight iron dextran vs single‐dose ferumoxytol for the treatment of iron deficiency. Issue 12 (12th October 2020) - Cohen, Jonathan; Khudanyan, Arpine; Lu, Jessica; Wing, Jason; Olson, Sven; Deloughery, Thomas; Shatzel, Joseph J.
Abstract: There are multiple intravenous (IV) iron formulations available, of which several may be administered as single‐dose infusions such as low‐molecular weight iron dextran (LMWID), ferumoxytol, ferric carboxymaltose, and ferric derisomaltose. However, administration of ferumoxytol as a single‐dose infusion is off‐label as it is approved as a two‐dose series. Previous studies of ferumoxytol alone support the effectiveness and safety of the single‐dose regimen, but there is a paucity of data directly comparing single‐dose ferumoxytol to other single‐dose IV iron formulations. This multicenter cohort study sought to affirm the safety and effectiveness of single‐dose ferumoxytol compared to single‐dose LMWID. Overall, 906 patients who received single‐dose LMWID (n = 439) or ferumoxytol (n = 467) were identified, of whom 351 met criteria for the primary effectiveness endpoint defined as median change in hemoglobin (Hb), hematocrit (Hct), and ferritin 8 to 12 weeks from baseline. All 906 patients were included for the secondary analysis evaluating the incidence of adverse events (AE) and requirement of additional IV iron infusions. Median change in Hb (LMWID 0.5 g/dL; ferumoxytol 0.8 g/dL; P = .24), Hct (LMWID 1.1%; ferumoxytol 1.25%; P = .89), and ferritin (LMWID 87 ng/dL; ferumoxytol 71 ng/dL; P = .47) was not significantly different between groups. Both groups experienced similar rates of AEs (LMWID 2.3%; ferumoxytol 2.8%; P = .63). The LMWID patients more frequently required additional IV iron infusions (LMWID 28.5%; ferumoxtyol 16.1%; P < .001). These findings support that single‐dose ferumoxytol is effective and safe, and that patients may require fewer additional infusions compared to patients who received LMWID.